Islamic Aesthetic Philosophy in Arabic Calligraphy - Kholili Hasib (Universitas Negeri Malang, 2021)
This article describes the aesthetic value of Arabic calligraphy or khat. This study of khat art's aesthetic value aims to reveal the model and philosophy of Arabic calligraphy as an Islamic work of art. The analysis in this article employed descriptive methods and two approaches, notably philosophical and historical. The model and philosophy of a work of Islamic art are influenced by the aqliyyah influence of an artist, according to the analysis. Because religious values influence an artist's perspective, his artwork contains an aesthetic philosophy that is also religious. For example, since the arrival of the muballigh from Arabia, the emergence of Islamic arts in the archipelago has been inextricably linked to the process and development of Islamization activities. The propagators of Islam use art and da'wah in their work. In a nutshell, physical and metaphysical beauty are both present in Arabic calligraphy. Physical beauty is pursued in the creation of calligraphy that has smooth and pleasing forms to the eye. The art form of calligraphy contains metaphysical beauty in the form of beautiful and good messages. These messages can be in the form of instruction (ta'limiyyah) or simply facts about da'wah.